PELATIHAN PEMANFAATAN GAS LPG SEBAGAI BAHAN BAKAR ALTERNATIF GENSET UNTUK MASYARAKAT NELAYAN - Yovan Witanto; Hendra Hendra; Angky Puspawan (DHARMA RAFLESIA, 2018)
This community service aimed at improving the knowledge and skills of the fishermen community of Pantai Jakat Bengkulu city in using gas fuel converted from liquid fuel. The community service was conducted in the form of a traning. The activities involved the fishermen in installing the converter kit of a gas fuel; trying out the genset which used the gas fuel; and evaluating the performance of the genset. After the training, the participant were asked to give opinion about the possibility of using the converted gas in their day to day fishing activities. The results of the training showed that the fishermen have a positive responses toward the use of the gas fuel for the genset. However, they still have some worries toward the safety of using the converted gas fuel.  Keywords: Genset, Gas Fuel